Preparation and Characterization of rGO/Fe3O4/MnO2 Nanocomposite for Enhanced Removal of Terasil Black Dye in Waste Water Treatment - Ismail , Ali Fadhil; Al-Abodi , Entisar E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This study focuses on the synthesis and characterization of a ternary nanocomposite comprising reduced graphene oxide (rGO), magnetite (Fe3O4), and manganese dioxide (MnO2) nanoparticles (NPs). The aim of using it is to remove Terasil Black dye from water, particularly in textile industries. The nanocomposite was created using a co-precipitation method, followed by physical bonding with MnO2 NPs. The structural properties, surface morphology, and elemental composition were evaluated through X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), and energy-dispersive X-ray (EDX) analysis. The XRD results confirmed the presence of an amorphous phase along with distinct diffraction peaks that correspond to specific lattice planes. FESEM images showed irregular particle shapes and significant agglomeration. EDX analysis confirmed the presence of the expected elements. The adsorption isotherms displayed (S) patterns as classified by Giles, suggesting that the dye ions align vertically relative to the nanocomposite's surface. The adsorption process is endothermic and primarily driven by physical interactions, which become more significant at higher temperatures. Analyzing the adsorption data indicates that the Freundlich isotherm model better describes this process, suggesting a non-uniform surface. This model demonstrates that chemical and physical adsorption processes were involved, with their contributions varying across different temperature ranges. The findings provide valuable insights into the thermodynamics and kinetics of dye adsorption on rGO/Fe3O4/MnO2 nanocomposites, which are essential for optimizing their application in waste water treatment.